Educational influences on student academic attainment: a multi-level analysis in the context of Bangladesh - Jahan, Monira (2012)
Bangladesh has made significant progress in terms of improving student access and gender disparity at primary and secondary levels of education. Currently, the major concern is the quality of education. In the national interest, the government of Bangladesh has undertaken a number of intervention programmes to increase the quality of primary and secondary education. Recently, researchers and practitioners are more engaged in investigating the quality of education, particularly at primary and secondary levels, where they have focused on the following themes: • internal efficiency • achievement of basic competency • acquisition of terminal competencies • teacher education • private expenditure on education There has been little application of School Effectiveness Research (SER) in Bangladesh, though SER became one of the most important educational movements and discourses in the West and came to prominence very rapidly in other developed and developing countries, namely Australia, Canada, South Africa, Indonesia, China and India. Therefore, the current study is significant in that it explores contemporary issues in the Bangladesh education system, which influence student academic attainment and present the findings of the first school effectiveness study in Bangladesh using multi-level analysis.